Pertimbangan Hakim terhadap Akibat Hukum dari Tindakan Persaingan Curang (Passing-Off) dalam Sengketa Desain Industri - Wibowo, Eko Putro; Setiawan, Dedi; Kuswanto, Teguh Junian; Hadyan, Tutuko Rakha; Pratama, Din Eri (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to examine the legal consequences of passing off in industrial design disputes with a case study of Court Decision Number 78/Pdt.Sus HKI/Desain Industri/2022/PN Niaga Jkt.Pst regarding suitcase generator products. Passing off is understood as the act of imitating or copying an industrial design legally owned by another party with the intention of obtaining unlawful profits through consumer confusion. The research method used is normative juridical, analysing relevant legislation, legal doctrine, and court decisions. The results of the study show that passing off has significant legal implications in the civil, administrative, and economic spheres. From a civil perspective, the defendant is required to stop the distribution of counterfeit products and may be liable for damages. From an administrative perspective, court decisions reinforce the exclusive rights of industrial design owners as a form of state protection. Meanwhile, from an economic and reputational perspective, design owners obtain compensation for material and immaterial losses caused by counterfeit products. These decisions also have a preventive effect on other businesses to respect the intellectual property rights of others. This study emphasises the importance of legal protection for industrial designs as an effort to maintain a healthy business climate, encourage creativity, and provide legal certainty for rights holders. However, the effectiveness of legal protection still faces challenges, particularly in relation to rampant violations even though the designs have been registered. Therefore, it is necessary to strengthen law enforcement and increase business actors' legal awareness so that the protection of industrial designs in Indonesia can be optimised.